Ag2CrO4 nanoparticles loaded on two-dimensional large surface area graphite-like carbon nitride sheets: simple synthesis and excellent photocatalytic performance. Issue 13 (3rd March 2016) - Shi, Lei; Liang, Lin; Wang, Fangxiao; Liu, Mengshuai; Sun, Jianmin
Abstract : Smaller Ag2 CrO4 nanoparticles were highly dispersed on the large surface area g-C3 N4 sheets and exhibited significantly enhanced photocatalytic activity. Abstract : Graphite-like carbon nitride (g-C3 N4 ) with a large surface area was prepared through thermal condensation of guanidine hydrochloride at 650 °C. Various amounts of silver chromate (Ag2 CrO4 ) nanoparticles with small size were highly loaded on the g-C3 N4 by a simple co-precipitation method at room temperature. The chemical constituents, surface structure and optical properties of the resultant Ag2 CrO4 /g-C3 N4 composites were thoroughly characterized. And the photocatalytic performances were evaluated by degradation of Rhodamine B (RhB) and phenol, the experimental results indicated that the as-prepared Ag2 CrO4 /g-C3 N4 composites presented excellent photocatalytic activity under visible-light irradiation. With the mass ratio of Ag2 CrO4 to g-C3 N4 at 1 : 2, the Ag2 CrO4 /g-C3 N4 composites exhibited optimal photocatalytic activity for degrading RhB, approximately 6.1 and 10.4 times higher than those on pure g-C3 N4 and bare Ag2 CrO4 particles. The improved photocatalytic activity was mainly attributed to the combined effect including the larger surface area, highly dispersed smaller Ag2 CrO4 nanoparticles, stronger visible absorption and higher charge separation efficiency of the Ag2 CrO4 /g-C3 N4 composites. Moreover, the possible mechanism for the photocatalytic activity was tentatively proposed.